Conditioning Electrical Stimulation Is Superior to Postoperative Electrical Stimulation in Enhanced Regeneration and Functional Recovery Following Nerve Graft Repair. (April 2020) - Senger, Jenna-Lynn B.; Chan, Ashley W. M.; Chan, K. Ming; Kwan-Wong, Terence; Acton, Leah; Olson, Jaret; Webber, Christine A.
Background . Autologous nerve graft is the most common clinical intervention for repairing a nerve gap. However, its regenerative capacity is decreased in part because, unlike a primary repair, the regenerating axons must traverse 2 repair sites. Means to promote nerve regeneration across a graft are needed. Postoperative electrical stimulation (PES) improves nerve growth by reducing staggered regeneration at the coaptation site whereas conditioning electrical stimulation (CES) accelerates axon extension. In this study, we directly compared these electrical stimulation paradigms in a model of nerve autograft repair. Methods . To lay the foundation for clinical translation, regeneration and reinnervation outcomes of CES and PES in a 5-mm nerve autograft model were compared. Sprague-Dawley rats were divided into: ( a ) CES, ( b ) PES, and ( c ) no stimulation cohorts. CES was delivered 1 week prior to nerve cut/coaptation, and PES was delivered immediately following coaptation. Length of nerve regeneration (n = 6/cohort), and behavioral testing (n = 16/cohort) were performed at 14 days and 6 to 14 weeks post-coaptation, respectively. Results . CES treated axons extended 5.9 ± 0.2 mm, significantly longer than PES (3.8 ± 0.2 mm), or no stimulation (2.5 ± 0.2 mm) ( P < .01). Compared with PES animals, the CES animals had significantly improved sensory recovery (von Frey filament testing, intraepidermal nerve fiber reinnervation) ( P < .001) and motor reinnervation (horizontal ladder, gait analysis, nerve conduction studies, neuromuscular junction analysis) ( P < .01). Conclusion . CES resulted in faster regeneration through the nerve graft and improved sensorimotor recovery compared to all other cohorts. It is a promising treatment to improve outcomes in patients undergoing nerve autograft repair.